(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
3D Printing is influencing the medical and surgical fields in many positive and interesting ways. The PD3D lab at the University of Central Florida has been working with many applications including Patient Specific Pre-Surgical Planning Models, Patient Specific Medical Device Development, Surgical Skills Task Trainers, Anatomical Training Models and Procedural Simulation Manikins. Through the advances of Polyjet 3D Printing and patented methods of creating composite structured materials, the tunability and fidelity are being develop to simulate realistic tissues that look, feel and behave like human tissues.